+0  
 
0
116
1
avatar

\(If $f(x) = 2x + 3$ and $g(x) = 3x - 2$ find $\frac{f(g(f(2)))}{g(f(g(2)))}$. Express your answer in the form $\frac{a}{b}$.\)

Please help!

 Jun 18, 2019

Best Answer 

 #1
avatar+8842 
+2

f(x)  =  2x + 3          and          g(x)  =  3x - 2

 

f( g( f(2) ) )   =   f( g( 7 ) )   =   f(  19  )   =   41

 

g( f( g(2) ) )   =   g( f( 4 ) )   =   g( 11 )   =   31

 

And so...

 

\(\dfrac{f(\ g(\,f(2)\,)\ )}{g(\ f(\,g(2)\,)\ )}\ =\ \dfrac{41}{31}\)_

 Jun 18, 2019
 #1
avatar+8842 
+2
Best Answer

f(x)  =  2x + 3          and          g(x)  =  3x - 2

 

f( g( f(2) ) )   =   f( g( 7 ) )   =   f(  19  )   =   41

 

g( f( g(2) ) )   =   g( f( 4 ) )   =   g( 11 )   =   31

 

And so...

 

\(\dfrac{f(\ g(\,f(2)\,)\ )}{g(\ f(\,g(2)\,)\ )}\ =\ \dfrac{41}{31}\)_

hectictar Jun 18, 2019

8 Online Users

avatar